Instagram Live as a Promotional Media for Inacraft Exhibitions - Antasari, M Rizky (CV. Publikasi Indonesia, 2025)
In an era of rapid social media development, Instagram continues to innovate to maintain its position as a leading platform. The platform is widely used by event organizers—such as music festivals, seminars, and exhibitions—to remain competitive and keep pace with technological advancements. Event organizers require creative and innovative approaches in disseminating information, conveying messages, and conducting promotions, one of which is through the use of Instagram. This research aims to analyze the use of Instagram’s live feature on the @weareinacraft account in promoting the Inacraft exhibition. This study employs a qualitative descriptive method, with findings indicating that Instagram’s live feature can expand audience reach, build closer and more sustainable relationships with followers, and create more personalized and dynamic interactions. With careful planning and production, Instagram Live has great potential as an effective and engaging promotional tool for events such as the Inacraft exhibition. These findings were analyzed using new media theory—which includes social interaction and social integration—and are associated with the concept of the 4Cs in social media use: context, communication, collaboration, and connection.